2012
DOI: 10.1016/j.surg.2012.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of interferon alpha using a novel Cox2-controlled adenovirus for pancreatic cancer therapy

Abstract: Background Combination therapy with interferon alpha (IFN) is correlated with improved survival in patients with pancreatic ductal adenocarcinoma (PDAc) but frequently presents side effects. We designed a novel targeted adenovirus with replication restricted to cyclooxygenase 2 (Cox2)-overexpressing PDAcs and hypothesize that the locally delivered therapeutic gene IFN can augment oncolytic effects while minimizing systemic toxicity. Methods IFN-expressing vectors were tested in vitro with the use of 4 PDAc c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 23 publications
1
30
0
2
Order By: Relevance
“…To further enhance the effect of an IFN-expressing adenovirus, our group developed an infectivity-enhanced, conditionally replicative adenovirus (CRAd) that is designed to selectively replicate and spread within pancreatic cancer cells expressing cyclooxygenase 2 (Cox2). The incorporation of the human IFN transgene into the E3 region of the adenovirus genome allows for a high concentration of IFN to be locally produced at the tumor site with each successful cycle of viral replication 21, 22 . To overcome the low infectivity and improve upon the oncolysis of conventional CRAds, the virus was designed to include an Ad5/Ad3 chimeric fiber and overexpression of the adenovirus death protein (ADP).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To further enhance the effect of an IFN-expressing adenovirus, our group developed an infectivity-enhanced, conditionally replicative adenovirus (CRAd) that is designed to selectively replicate and spread within pancreatic cancer cells expressing cyclooxygenase 2 (Cox2). The incorporation of the human IFN transgene into the E3 region of the adenovirus genome allows for a high concentration of IFN to be locally produced at the tumor site with each successful cycle of viral replication 21, 22 . To overcome the low infectivity and improve upon the oncolysis of conventional CRAds, the virus was designed to include an Ad5/Ad3 chimeric fiber and overexpression of the adenovirus death protein (ADP).…”
Section: Introductionmentioning
confidence: 99%
“…We have recently reported that this infectivity-enhanced, tumor-specific CRAd demonstrated a greatly improved oncolytic effect mediated by IFN overexpression. The virus was effective in both in vitro and in vivo settings, including a human pancreatic cancer xenograft model in nude mice 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Low CAR levels on target tumor cells have been a limiting factor with certain gene therapy approaches for some time, but modification of the adenovirus capsid proteins has been shown to improve infectivity in both HNSCCs as well as other cancers [33, 34]. Previously, our group has used an Ad5/Ad3 fiber in the setting of adenoviral therapy for pancreatic cancer [27]. Based on this experience, we have applied the same fiber modification to overcome the CAR deficiency for HNSCCs.…”
Section: Discussionmentioning
confidence: 99%
“…Ramon Alemany and Cristina Balgué) were recombined with the pAd-ΔE3-ADP-Luc adenoviral backbone as previously described [26]. Briefly, in the pAd-ΔE3-ADP-Luc structure, most of the non-essential adenovirus E3 genes were deleted (with the exception of the adenovirus death protein (ADP) which is designed to facilitate viral spread and oncolysis) and replaced with the luciferase reporter gene [26, 27]. …”
Section: Methodsmentioning
confidence: 99%
“…Human PC cells that underwent retrovirusmediated gene transfer of IL-2, IL-4, IL-6, IL-27 and granulocyte macrophage-colony stimulating factor (GM-CSF) showed significant retardation and even regression when inoculated into BALB/c nude mice [129,130] . In vivo gene delivery of IL-1β, IL-24, IFN-a, IFN-β and IFN-γ by different viral vectors have been proved to lead to significant tumor growth inhibition in many PC models [131][132][133][134][135] . In addition, combined application of cytokine transfection and traditional chemotherapy, and combining immune genes with either tumor suppressor genes or suicide genes, are also common strategies in cancer immunogen therapy.…”
mentioning
confidence: 99%